Bulgakov code in the novel of V. Pelevin “Chapaev and Empty” - Склярова, Тетяна Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The relevance of the research is due to the significance of the Bulgakov intertext in the novel by V. Pelevin. The article shows that the Bulgakov code “Chapaeva and Void” turned out to be practically outside the zones of scientific interest. Meanwhile, his analysis and understanding of man and the novel. Pelevin writes “Surfaces”, “Masters and Margaritas”, like everything that makes them look like all works that demonstrate almost all structural levels: components, compositions, problems, subjects, character systems and motifs.The study of Bulgakov’s intertext allows us to say that Pelevin uses Bulgakov’s novel “The Master and Margarita” as the main suit, and the Bulgakov’s code, in addition to the Buddhist one, is fundamentally important for the interpretation of “Chapaev and Void”. Pelevin conducts a kind of philosophical and religious dialogue with the classic. Bulgakov’s worldview is built on Christian values, which is most manifested in his “sunset” novel. The axiology of the novel is subordinate to Christian ideology, in particular, its moral component. As you know, in “Chapaev and the Void” certain aspects of Orthodoxy are rigidly parodyed. However, the dispute with the predecessor does not occur in the aspect of the deconstruction of the Christian myth and the presentation of the more relevant - the Buddhist. The author of "Chapaev and the Void" doubts that it is based on all possible patterns, that is, history has nothing to do with spiritual views, when individual ways of finding harmony are revealed through rejection of previous moral and ethical programs.The novel "Chapaev and the Void", as well as "The Master and Margarita", can be defined as two-address texts. Turning to the broad readership, Pelevin creates a comfortable and recognizable system of signs generated by the mass culture. Each element of his novel supposes inconsistency and ambiguity, which allows the author to pose the most important philosophical problems.